2008
DOI: 10.3928/08910162-20081101-04
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Tools to Reduce Workplace Violence

Abstract: The U.S. health care system is in the beginning of a crisis that can barely be comprehended. If projections are accurate, the demand for nurses will increase 40% and a 400,000-hour full-time equivalent registered nurse shortfall will occur by 2020. Not only are nurses leaving the field, but fewer candidates are entering. The reasons are unclear, but research has shown that nursing is a dangerous occupation--four times more dangerous than most other occupations. Protection from an unsafe workplace is guaranteed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…It has been reported that health care professionals, and nurses in particular, are more commonly bullied than those in other professions (Gallant-Roman, 2008). It was also found in this study that most nurses received negative criticism although they reported performing their jobs properly, were held responsible for others' mistakes, and were assigned duties outside their work responsibilities.…”
Section: Discussionmentioning
confidence: 50%
“…It has been reported that health care professionals, and nurses in particular, are more commonly bullied than those in other professions (Gallant-Roman, 2008). It was also found in this study that most nurses received negative criticism although they reported performing their jobs properly, were held responsible for others' mistakes, and were assigned duties outside their work responsibilities.…”
Section: Discussionmentioning
confidence: 50%
“…Although patient violence against nurses has been identified in current nursing literature, such as Pich et al, (2010) and Gallant-Roman (2008), as a serious occupational hazard, there is a lack of simple screening tools to identify the potential for violence in this setting (Wilkes et al, 2010). Early recognition of the warning signs of patient violence may reduce the incidence of occurrence or increase preparedness for such an event.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…There is generally a more infrequent reference to the risk of violence in the health care sector, although the incidence is significantly higher and often underreported (Child & Mentes, 2010). Gallant-Roman (2008) reported that the cost of workplace violence was estimated to be $4.2 billion annually in 2001. Nurses also reported workplace violence twice as often as any other healthcare provider.…”
Section: Workplace Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Ramos (cited in Gallant-Roman, 2008) indicated that a tough, socially dominant personality is a strong predictor of longevity in nursing. Ramos (cited in Gallant-Roman, 2008) indicated that a tough, socially dominant personality is a strong predictor of longevity in nursing.…”
Section: Tools and Strategiesmentioning
confidence: 99%